2012
DOI: 10.1038/npp.2012.36
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Dissection of the Role of Cannabinoid Type-1 Receptors in the Emotional Consequences of Repeated Social Stress in Mice

Abstract: The endocannabinoid system (ECS) tightly controls emotional responses to acute aversive stimuli. Repeated stress alters ECS activity but the role played by the ECS in the emotional consequences of repeated stress has not been investigated in detail. This study used social defeat stress, together with pharmacology and genetics to examine the role of cannabinoid type-1 (CB 1 ) receptors on repeated stressinduced emotional alterations. Seven daily social defeat sessions increased water (but not food) intake, sucr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
118
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 133 publications
(131 citation statements)
references
References 97 publications
(157 reference statements)
11
118
1
1
Order By: Relevance
“…On the contrary, CUS mice showed reduced increase in 2-AG by JZL184, no combo-induced synergism, and consequently, no drug-induced anxiogenic and depression-like effects as seen in controls. This leads to the speculation that the druginduced exacerbation/over-activation of the 2-AG signaling, supposedly occurring in the control mice, does not happen in the CUS mice, because their 2-AG signaling is already perturbated by chronic stress exposure (Gorzalka et al, 2008;Dubreucq et al, 2012). Further investigations must be pursued to elucidate the mechanisms underlying these drug-induced effects.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, CUS mice showed reduced increase in 2-AG by JZL184, no combo-induced synergism, and consequently, no drug-induced anxiogenic and depression-like effects as seen in controls. This leads to the speculation that the druginduced exacerbation/over-activation of the 2-AG signaling, supposedly occurring in the control mice, does not happen in the CUS mice, because their 2-AG signaling is already perturbated by chronic stress exposure (Gorzalka et al, 2008;Dubreucq et al, 2012). Further investigations must be pursued to elucidate the mechanisms underlying these drug-induced effects.…”
Section: Discussionmentioning
confidence: 99%
“…Within the amygdala, this effect appears to be quite prominent as exposure of both rats and mice to restraint stress causes a reduction in the tissue levels of AEA (Gray et al, 2015;Hill et al, 2009c;Patel et al, 2005b;Rademacher et al, 2008). Similarly, both acute restraint stress and social defeat stress have been found to reduce AEA content within the hippocampus (Dubreucq et al, 2012;Wang et al, 2012b). This reduction in AEA content is, at least in part, mediated by an increase in AEA hydrolysis by FAAH as acute stress increases FAAH activity within the amygdala (Gray et al, 2015;Hill et al, 2009c).…”
Section: Effects Of Acute Stress On Aea Brain Levelsmentioning
confidence: 96%
“…Interestingly, this effect appears to be conserved throughout the lifespan as early life stress in the form of maternal separation has also been shown to reduce AEA content within the hippocampus (Marco et al, 2013). Unlike the consistency seen in the amygdala and hippocampus, the mPFC seems to be somewhat of a more complex structure as exposure to swim stress has been found to produce a robust reduction of AEA content (McLaughlin et al, 2012), but neither acute restraint (Gray et al, 2015;Hill et al, 2011b;Rademacher et al, 2008) nor acute social defeat (Dubreucq et al, 2012) were found to have any effect on AEA content in the mPFC. Similarly, restraint stress was found to have no effect on FAAH mRNA, protein, or activity within the mPFC (Gray et al, 2015;Navarria et al, 2014).…”
Section: Effects Of Acute Stress On Aea Brain Levelsmentioning
confidence: 99%
“…WT and TPH2-CB 1 -KO littermates (19), in which the CB 1 gene is deleted in the raphe nucleus but not in other brain regions (Fig. 1C and Fig.…”
Section: Cb 1 Receptors In Different Brain Neuron Types Are Dispensabmentioning
confidence: 99%